Deep RNA Sequencing Uncovers a Repertoire of Human Macrophage Long Intergenic Noncoding RNAs Modulated by Macrophage Activation and Associated With Cardiometabolic Diseases. Issue 11 (13th November 2017) - Zhang, Hanrui; Xue, Chenyi; Wang, Ying; Shi, Jianting; Zhang, Xuan; Li, Wenjun; Nunez, Sara; Foulkes, Andrea S.; Lin, Jennie; Hinkle, Christine C.; Yang, Wenli; Morrisey, Edward E.; et al.
Abstract : Background: Sustained and dysfunctional macrophage activation promotes inflammatory cardiometabolic disorders, but the role of long intergenic noncoding RNA (lincRNA) in human macrophage activation and cardiometabolic disorders is poorly defined. Through transcriptomics, bioinformatics, and selective functional studies, we sought to elucidate the lincRNA landscape of human macrophages. Methods and Results: We used deep RNA sequencing to assemble the lincRNA transcriptome of human monocyte‐derived macrophages at rest and following stimulation with lipopolysaccharide and IFN‐γ (interferon γ) for M1 activation and IL‐4 (interleukin 4) for M2 activation. Through de novo assembly, we identified 2766 macrophage lincRNAs, including 861 that were previously unannotated. The majority (≈85%) was nonsyntenic or was syntenic but not annotated as expressed in mouse. Many macrophage lincRNAs demonstrated tissue‐enriched transcription patterns (21.5%) and enhancer‐like chromatin signatures (60.9%). Macrophage activation, particularly to the M1 phenotype, markedly altered the lincRNA expression profiles, revealing 96 lincRNAs differentially expressed, suggesting potential roles in regulating macrophage inflammatory functions. A subset of lincRNAs overlapped genomewide association study loci for cardiometabolic disorders. MacORIS (macrophage‐enriched obesity‐associated lincRNA serving as a repressor of IFN‐γ signaling), a macrophage‐enriched lincRNA not expressed in mouse macrophages, harbors variants associated with central obesity. Knockdown of MacORIS, which is located in the cytoplasm, enhanced IFN‐γ–induced JAK2 (Janus kinase 2) and STAT1 (signal transducer and activator of transcription 1) phosphorylation in THP‐1 macrophages, suggesting a potential role as a repressor of IFN‐γ signaling. Induced pluripotent stem cell–derived macrophages recapitulated the lincRNA transcriptome of human monocyte‐derived macrophages and provided a high‐fidelity model with which to study lincRNAs in human macrophage biology, particularly those not conserved in mouse. Conclusions: High‐resolution transcriptomics identified lincRNAs that form part of the coordinated response during macrophage activation, including specific macrophage lincRNAs associated with human cardiometabolic disorders that modulate macrophage inflammatory functions.